Identification of Differential Responses to an Oral Glucose Tolerance Test in Healthy Adults - Morris, Ciara; O’Grada, Colm; Ryan, Miriam; Roche, Helen M.; Gibney, Michael J.; Gibney, Eileen R.; Brennan, Lorraine (PloS one, 2013)
In recent years an individual's ability to respond to an acute dietary challenge has emerged as a measure of their biological flexibility. Analysis of such responses has been proposed to be an indicator of health status. However, for this to be fully realised further work on differential responses to nutritional challenge is needed. This study examined whether metabolic phenotyping could identify differential responders to an oral glucose tolerance test (OGTT) and examined the phenotypic basis of the response. A total of 214 individuals were recruited and underwent challenge tests in the form of an OGTT and an oral lipid tolerance test (OLTT). Detailed biochemical parameters, body composition and fitness tests were recorded. Mixed model clustering was employed to define 4 metabotypes consisting of 4 different responses to an OGTT. Cluster 1 was of particular interest, with this metabotype having the highest BMI, triacylglycerol, hsCRP, c-peptide, insulin and HOMA- IR score and lowest VO2max. Cluster 1 had a reduced beta cell function and a differential response to insulin and c-peptide during an OGTT. Additionally, cluster 1 displayed a differential response to the OLTT. This work demonstrated that there were four distinct metabolic responses to the OGTT. Classification of subjects based on their response curves revealed an "at risk" metabolic phenotype.